Development of the Chanting Model in the Current Thai Society - Sonsiri, Ph.D., Wanchai; Chupong, Ph.D., Pol.L/C. Pennapa (Journal of Dhamma for Life, 2024)
This article aims to analysis the development of Chanting in the current Thai societies. From the study, it is found that the Chanting is the saying of the praising words to the persons whom we respect. Such the action will help every person to be mentally peaceful, to be of mindfulness and the wisdom and to be the ability to carry out the life. The ancient Thai societies received the culture in Chanting from Sri LanKa and were of the development of the Mantras Chanting to be in compliance with their own cultures to continue the Dhammas to be permanent. Beside this point, there is still the study of the Pali Language for knowing the Doctrinal principle. The present way of Chanting the Mantras in the present Thai societies is of the order or the pattern more than the Buddha’s time, because there has been the fixation of the text of Chanting the Mantras which are suitable for the making of the merits. Such the method is the one which the ancient teachers had taught to us and is the one which we should practice as ancient teachers taught to us to be the way of leading our lives to be of happiness.